Smart Water Tank Web-based - Bekti Nurdiyana, Linda; Wahyu Ciptadi, Prahenusa; Hardyanto, R. Hafid (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2022)
In this modern era, automatic equipment dominates human life because it can ease the burden of human work. A variety of practical and flexible electronic devices have been created to help people more easily meet their needs. This research designed an automated water tank monitoring system using microcontrollers and utilizing the internet and websites as visualization of monitoring data. This smart water tank consists of pH sensors, turbidity sensors, and TDS sensors. In addition, there is a water level to detect the water level in the reservoir, a solenoid valve as an automatic faucet, and water flow to calculate the discharge of water that fills the reservoir. When tds sensors and turbidity sensors detect water in a bad state it will automatically drain the Tandon. After the water drain is drained, the water level will be detected and then the water pump will automatically turn on. The purpose of this smart water tank is to make it easier for users to monitor the water tank in real time and accurately. The results of the test were carried out that every time the water detects turbidity levels above 25 NTu and Tds above 1000 mg / l then the water will be automatically wasted even though the reservoir is in full condition. The test results also proved the system is able to work by sending water data and displaying it on the web www.tandonair.online.